A Multi-Criteria Decision-Making Model for Determining Material Storage Locations Using the AHP–TOPSIS Method: A Study at PT PLN (Persero) UP2D Lampung - Yus Octavian; Suparno (Journal Research of Social Science, Economics, and Management, 2026)
PT PLN (Persero) UP2D Lampung faces limitations in internal warehouse capacity, requiring some materials to be stored at other units located up to 46.8 km away. This situation increases storage and transportation costs and reduces the efficiency of inventory management. This study aimed to develop a multi-criteria decision-making model for determining the optimal material storage location by integrating the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS). The evaluation criteria were identified through discussions with subject-matter experts and materials management personnel, resulting in four criteria and six sub-criteria. The four evaluation criteria were land capacity, resources, management quality, and operational efficiency. The six sub-criteria comprised warehouse area, the number of employees and outsourced personnel, the availability of truck drivers, maturity level, inventory turnover (ITO), and service area. The AHP method was used to determine the weights of the criteria and sub-criteria, whereas TOPSIS was applied to evaluate and rank the alternative warehouse locations. A total of five candidate storage locations were evaluated. The results indicated that the Tanjung Karang Warehouse was the preferred material storage location, achieving the highest preference score of 0.695. These findings demonstrate that integrating AHP and TOPSIS provides an objective, systematic, and measurable decision-making framework for determining material storage locations and offers a practical decision-support tool for warehouse management at PT PLN (Persero).